Application of the Minimalization of Maximal Error Method in Transformation by Polynomial Approximation - Tenzer, Robert (Communications - Scientific letters of the University of Zilina, 2000)
The least square method is generally used for an estimation of the coefficients of polynomial transformation. The paper describes the rationalization of polynomial approximation by the minimization of maximal error model (Chebyshew approximation).